Contour Erasure and Filling-in: New Observations. (April 2014) - Anstis, Stuart; Greenlee, Mark W.
Contour erasure is a newly established form of flicker adaptation that diminishes the saliency of object edges leading to their complete disappearance (Anstis, S.2013 . Journal of Vision, 13 (2):25, 1–14). If these "disappeared" objects are then viewed on textured backgrounds, the observers experience filling-in, the illusory sense of background completion in the absence of physical input. In a series of observations, we demonstrate that contour erasure can greatly speed up the filling-in (or fading) of brightness. Based on these observations, we suggest that contour adaptation happens early in the magnocellular pathways.